Pengaruh Metode Pembelajaran Berbasis Adaptasi Teknologi Terhadap Motivasi Belajar Siswa SD Inpres Borong Jambu II Kota Makassar - Karolus D. Dari; Satriawati; R. Supardi; Cahyati (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This study aimed to determine the effect of technology adaptation-based learning methods on student motivation in class V/B SD Inpres Borong Jambu II Makassar City. This research is a Pre-Experimental experimental research using a quantitative approach. The sample of this research is class V/B SD Inpres Borong Jambu II, totaling 30 people. The research instruments used were observation sheets and questionnaires to strengthen students’ learning motivation. After analyzing the data, the authors found that the implementation of the technology adaptation- based learning method with a score of 3.5 in the very good category and student activities with a score of 3.4 in the good category. The pretest score on student responsens using technology adaptation- based learning methods is 73.23 and posttest score for student responses to technology-based learning methods with a score of 88.20. so it can be concluded that the learning motivation of students in class V/B SD Inpres Borong Jambu II Makassar city by using learning methods based on technology adaptation is very effective.